Executive Function Is Selectively Impaired in Old Age Bipolar Depression - Caixeta, Leonardo; Soares, Vânia L. D.; Vieira, Renata T.; Soares, Cândida D.; Caixeta, Victor; Ferreira, Sandra B.; Aversi-Ferreira, Tales A. (Frontiers in Psychology, 2017)
Background: Little is known about the cognitive signature of bipolar disorder (BD) in elderly brains. The neuropsychological features of depressive elderly with early-onset BD are largely unknown. This issue is relevant because cognitive impairment can produce an additional impact on the already compromised functionality of elderly with BD. The aim of this study is to assess executive functions (EFs) in the depressive phase of elderly outpatients with early-onset BD. Methods: Forty-nine elderly outpatients with early-onset BD were assessed with several neuropsychological tests for EF in the depressive phase of the disorder. Results: Executive dysfunction is very common in old age bipolar depression. Thirteen patients (26.5%) had a pseudodementia presentation. The worst performances were observed in the following tests: Trail Making B, Stroop Test 3, Backward Digit Span and Wisconsin Card Sorting Test. Conclusion: Executive dysfunction profile in elderly BD is complex and heterogeneous, but most cases display difficulties in working memory, inhibitory control, mental flexibility, and information processing speed. The performance of elderly with bipolar depression in executive assessment can be divided into two main categories: (1) Single EF domain impairment; and (2) Multiple EF domain impairment with or without a pseudodementia syndrome. Executive dysfunction in old age bipolar depression may be explained by lack of sufficient mental energy to run those cognitive processes that require larger amounts of effort to be performed.